2020
DOI: 10.22159/ijpps.2020v12i8.38363
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Utilization of Drug-Information Resources of Healthcare Providers in an Academic Tertiary Care Center

Abstract: Objective: To investigate the drug-related information needs of healthcare providers (HCPs), their utilization of drug information resources as well as the main factors influencing the selection of resources.Methods: A total of 393 HCPs were conveniently selected and invited to complete a questionnaire. Stratified sampling was used for the three subpopulations of physicians, pharmacists, and nurses. The questionnaire was coded, validated, and analyzed using the Statistical Package for the Social Sciences (SAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It has been reported that healthcare providers use the internet most frequently to gather health, medical or prescription drug information (De Leo et al, 2006;Podichetty et al, 2006;Hartzband, Groopman, 2010;Younger, 2010). It has been reported that digital resources of drug information were used more frequently by healthcare professionals than traditional resources such as printed material, consulting a clinical pharmacist or calling drug information center despite the untrustworthy and unreliable of internet and electronic open-access resources (Alakeel, Almutairi, Layqah, 2020). McGettigan et al (2001) reported that the sources of prescribing information of greatest practical importance are those based on the medium of personal contact, primarily by hospital prescribers' peers in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that healthcare providers use the internet most frequently to gather health, medical or prescription drug information (De Leo et al, 2006;Podichetty et al, 2006;Hartzband, Groopman, 2010;Younger, 2010). It has been reported that digital resources of drug information were used more frequently by healthcare professionals than traditional resources such as printed material, consulting a clinical pharmacist or calling drug information center despite the untrustworthy and unreliable of internet and electronic open-access resources (Alakeel, Almutairi, Layqah, 2020). McGettigan et al (2001) reported that the sources of prescribing information of greatest practical importance are those based on the medium of personal contact, primarily by hospital prescribers' peers in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1990s there has been a lot of reliance on the internet sources among health sciences students and is projected to be a reliable source of information for patient care in future [ 20 , 21 , 22 , 23 ]. Whereas health professionals mostly relied on textbooks and colleagues before the year 2000 [ 21 ], most doctors and pharmacists have now been found to update their patient care knowledge via the internet including the use of search engines to find drug information [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Adams et al ( 2007 ), Akhigbe & Omuemu ( 2009 ), Alakeel et al ( 2020 ), Baird & Miller ( 2015 ), Baro & Ebhomeya ( 2013 ), Belcik ( 2011 ), Blair ( 2008 ), Borycki & Lemieux‐Charles ( 2008 ), Borycki et al ( 2009 ), Boström et al ( 2009 ), Çalışkan & Kaya ( 2016 ), Carrier ( 2013 ), Carter‐Templeton ( 2013 ), Cato & Bakken ( 2012 ), Christiansen ( 2010 ), Christiansen ( 2012 ), Dalheim et al ( 2012 ), Farokhzadian et al ( 2015 ), Gardner ( 2017 ), Gilmour et al ( 2012 ), Hamaideh ( 2017 ), Hellier & Cline ( 2016 ), Hoare et al ( 2013 ), Jansson & Forsberg ( 2016 ), Kilicli et al ( 2019 ), Klein‐Fedyshin ( 2015 ), Komolafe & Onatola ( 2008 ), Kosteniuk et al ( 2019 ), Kumaran & Chipanshi ( 2015 ), Kwekkeboom & Frese ( 2009 ), Lee et al ( 2019 ), Miller et al ( 2010 ), Mokhtar et al ( 2012 ), Muallem ( 2010 ), Neher et al ( 2015 ), Newman et al ( 2020 ), O'leary & Mhaolrúnaigh ( 2012 ), Profetto‐McGrath et al ( 2010 ), Randell et al ( 2009 ), Renolen & Hjälmhult ( 2015 ), Richmond & Mason ( 2016 ), Ricks & Ham ( 2015 ), Ross ( 2010 ), Rudman et al ( 2012 ), Scantlebury et al ( ...…”
mentioning
confidence: 99%